Identification of sapovirus infection among Japanese infants in a day care center - Akihara, Shiho; Phan, Tung Gia; Nguyen, Tuan Anh; Yagyu, Fumihiro; Okitsu, Shoko; Müller, Werner E.G.; Ushijima, Hiroshi (Journal of medical virology, 2005)
A total of 921 fecal specimens collected from 44 infants in a day care center in Tokyo, Japan during June 1999 to July 2000 were tested for the presence of sapovirus by reverse transcription‐polymerase chain reaction (RT‐PCR). Of 88 fecal specimens from infants with acute gastroenteritis, 2.3% (2) were found to be positive for sapovirus. Twenty‐two of 833 (2.6%) fecal specimens collected from asymptomatic infants were also infected with this virus. Another interesting feature was the demonstration of high incidence of sapovirus infection (95.5%, 21 of 22) identified in a single day care center, which was not due to viral shedding after the latest acute gastroenteritis. Sapovirus was subjected to genetic analysis by sequencing. Up to 4 of 24 sapoviruses (16.7%) were clustered into genogroup IV known as a rare group. Remarkably, majority (79.2%, 19 of 24) of sapovirus isolates detected in this study turned out to present one novel sapovirus genotype tentatively called GI/8. It was noteworthy to point out that the GI/8 sapovirus infection was apparently confined only within the period of 9 weeks (44th through 52nd weeks). This pattern of infection implied the outbreak of asymptomatic GI/8 sapovirus infection in these subjects. The findings clearly indicate genogroup I sapovirus can be classified into eight genotypes. This is the first report to underscore that sapovirus pathogen causes not only clinical manifestations of acute gastroenteritis but also asymptomatic infection in infants in day care centers in Japan. J. Med. Virol. 77:595–601, 2005. © 2005 Wiley‐Liss, inc.